Stability analysis of first order homogeneous Sylvester system of Difference equations (International Journal of Engineering and Computer Science, 2023)
This paper presents a criteria for the analysis of Stability, Observability and Realizability criteria for the homogeneous first order Sylvester system. Stability, Observability and Realizability for homogeneous Lyapunov system are deduced as a particular case of our results.